Hibiscus sabdariffa Linn. (Roselle) polyphenols-rich extract prevents hyperglycemia-induced cardiac oxidative stress and mitochondrial damage in diabetic rats - Nur Liyana Mohammed Yusof,; Tengku Nurul Tasnim Tengku Affendi,; Fatin Farhana Jubaidi,; Satirah Zainal Abidin,; Siti Balkis Budin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cardiac mitochondrial damage plays a crucial role in the initiation of diabetic cardiomyopathy. Hibiscus sabdariffa Linn. (roselle) has been proven to prevent various pathological conditions, however it remains unclear whether roselle extract can attenuate diabetes-induced mitochondrial damage. This study aimed to investigate whether roselle polyphenol-rich extract (HPE) is able to ameliorate hyperglycemia-induced oxidative stress and mitochondrial damage in diabetic rats. Diabetes was induced by a single dose of streptozotocin (55 mg kg-1, intraperitoneally); and diabetic rats were then orally fed with 100 mg kg-1 of HPE (DM+Roselle) or 150 mg kg-1 of Metformin (DM+MET) daily for 4 weeks. Meanwhile, the control and untreated diabetic (DM) groups were only orally given normal saline. After 4 weeks of treatment, the results showed that DM+Roselle group significantly improved blood glucose level and lipid profile status (p<0.05) compared to the DM group. DM+Roselle group also had significantly (p<0.05) lower the level of thiobarbituric acid reactive substances (TBARS) and advanced oxidation protein product (AOPP) in cardiac homogenate than the DM group. HPE supplementation also significantly improved activities of total superoxide dismutase (SOD), SOD-2, catalase (CAT) and level of reduced glutathione (GSH) of the cardiac homogenate. Complex I activity of mitochondria respiratory chain also decreased significantly (p<0.05) in DM+Roselle group as compared to the DM group. Observations using electron microscope showed that mitochondria in the DM+Roselle group appeared more organized compared to the DM group. In conclusion, these results highlight the potential of HPE as a protective agent against oxidative stress and mitochondrial damage in diabetic condition.